2002
DOI: 10.1002/jsfa.1235
|View full text |Cite
|
Sign up to set email alerts
|

Influence of curcuma (Curcuma xanthorrhiza Roxb) on lipid metabolism in rabbits

Abstract: The efficacy of curcuma (Curcuma xanthorrhiza) in lowering blood plasma lipid was evaluated in rabbits. Forty male New Zealand white rabbits (2.3 kg) were divided into four equal groups and offered isoatherogenic diets with no curcuma, low curcuma (2 g kg À1 ), medium curcuma (3 g kg À1 ) and high curcuma (4 g kg À1 ) for 120 days. Faeces and feed samples were collected. Body weight was measured weekly. Blood samples at 1, 2 and 4 months and liver samples at the last blood collection were taken. Curcuma did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…On the other hand, Lee et al (2003) failed to show any hypocholesterolemic effects of the active items as cinnamaldehyde. Wientarsih et al (2002) reported that Curcuma longa supplementation to the rabbit diets significantly decreased LDL, total cholesterol and triglycerides concentrations in plasma. Where, inclusion of Curcuma longa in the rabbit diets led to an increase in the 3-hydroxy-3-methylglutaryl coenzyme reductase inhibitor activity (Wientarsih et al, 2002); thereby, the reduction of 3hydroxy-3-methylglutaryl coenzyme reductase resulted in a decrease in total cholesterol biosynthesis in rat cells (Amin et al, 1993).…”
Section: Results Illustrated Inmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Lee et al (2003) failed to show any hypocholesterolemic effects of the active items as cinnamaldehyde. Wientarsih et al (2002) reported that Curcuma longa supplementation to the rabbit diets significantly decreased LDL, total cholesterol and triglycerides concentrations in plasma. Where, inclusion of Curcuma longa in the rabbit diets led to an increase in the 3-hydroxy-3-methylglutaryl coenzyme reductase inhibitor activity (Wientarsih et al, 2002); thereby, the reduction of 3hydroxy-3-methylglutaryl coenzyme reductase resulted in a decrease in total cholesterol biosynthesis in rat cells (Amin et al, 1993).…”
Section: Results Illustrated Inmentioning
confidence: 99%
“…Wientarsih et al (2002) reported that Curcuma longa supplementation to the rabbit diets significantly decreased LDL, total cholesterol and triglycerides concentrations in plasma. Where, inclusion of Curcuma longa in the rabbit diets led to an increase in the 3-hydroxy-3-methylglutaryl coenzyme reductase inhibitor activity (Wientarsih et al, 2002); thereby, the reduction of 3hydroxy-3-methylglutaryl coenzyme reductase resulted in a decrease in total cholesterol biosynthesis in rat cells (Amin et al, 1993). The obtained results were in agreement with Alagawany et al (2016) who found that triglycerides, total cholesterol and low density lipoprotein concentrations were linearly and quadratically decreased with increasing the dietary proportion of turmeric.…”
Section: Results Illustrated Inmentioning
confidence: 99%
“…In rabbit mixed feeds with palm oil (PO) supplementation, CL has decreased acid detergent fibre (ADF) digestibility and increased ether extract (EE) digestibility. The use of curcuma in rabbit diets has been evaluated, because of its effects on lipid metabolism, by Wientarsih et al (2002), who observed enhanced fat and cholesterol excretion mediated through an acceleration of the lipid metabolism from the extrahepatic tissues to the liver.…”
Section: Introductionmentioning
confidence: 99%
“…According to Rise et al (2003), it totally inhibits the D6 and D5 desaturation steps, preserves the level of ALA, and decreases cholesterol synthesis. In a prolonged administration to rabbits, Wientarsih et al (2002) have observed that Curcuma xanthorrhiza significantly decreases LDL and triglyceride concentrations. Curcuma inclusion has led to an increase in the 3-hydroxy-3-methylglutaryl coenzyme (HMGCoA) reductase inhibitor activity (Wientarsih et al, 2002) and the inhibition of HMG-CoA reductase resulted in a decrease in cholesterol synthesis in rat cells (Amin et al, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation